Pertumbuhan dan Produksi Cabai Rawit Akibat Apliksi Pupuk Kandang Ayam dan NPK di Tanah Berpasir - Saijo; Fahruddin Arfianto; Rishon Oktaviandi (Fakultas Pertanian - UMJ, 2025)
Chili is a green product that is exceptionally prevalent with all bunches. Hence, seriously development procedures are critical to meet generation needs. The reason of this consider was to analyze and test the impact of chicken excrement and NPK medicines on the development and generation of chili plants in sandy soil. Conducted for 4 months from April-July 2024, found in Kereng Bangkirai Town, Sabangau Locale, Palangka Raya. The think about utilized a 2-factor Randomized Square Plan. The to begin with figure was chicken fertilizer treatment with 4 levels and the moment calculate was NPK treatment with 3 levels, so that 12 combinations were gotten. Each combination was rehashed 3 times, so that all 36 exploratory units were gotten. Based on the comes about of the consider, it appeared that all factors watched were as it were fertilizer treatment that had an impact, both development and surrender factors. The most noteworthy execution was appeared in plants treated with chicken fertilizer at a dosage of 40 t ha-1. The most elevated number of chili natural product harvests was 96.06 plants-1, the most noteworthy gathered natural product weight was 3x collect weighing 322.47 g plants-1. The collect potential is calculated based on the most elevated natural product weight, planting separate 40 x 40 cm, duplicated by the number of plant populace ha-1, coming about in 62,500 plants ha-1, so the gather potential is 20.15 t ha-1.